Causes and prevalence of factors causing infertility in a public health facility - Priyanka Sanjay Deshpande; Alka ShantiPrakash Gupta (Wolters Kluwer Medknow Publications, 2019)
Background: Infertility causes change according to local demographics. There is thus the need to find the causes of infertility in context to local population to aid and direct management strategies accordingly. Aims: The aims were to study the causes of infertility and to calculate the proportion of the individual factors contributing to it in the population coming to a tertiary level public health facility. Setting and Design: This cross-sectional, observational study was done in an infertility clinic in a medical college and government hospital. Materials and Methods: The study comprised 120 couples who came for infertility evaluation and treatment. Cause of infertility in the couple was assigned on the basis of history and examination findings. The prevalence of each cause was evaluated. Statistical Analysis: Results were tabulated, and the prevalence of individual factors was calculated. Intratable analysis was done using SPSS 16.0. Results: Primary infertility (57.5%) was more prevalent than secondary infertility (42.5%). Female factor accounted for 46.6% of the cases with polycystic ovarian syndrome (PCOS) being the leading cause (46%). Infertility was seen equally in lean and obese PCOS cases. Infectious causes such as pelvic inflammatory disease and tuberculosis were significantly associated with tubal factor infertility (P = 0.001). Infertility causes changed as the age of marriage increased. In couples married for less than 5 years, PCOS was the main cause whereas later,male factor and unexplained infertility were the most common causes seen. Male factor contributed to 20% of the cases of infertility, and both tobacco and alcohol consumption were significantly associated with abnormal semen reports (P = 0.001). Conclusion: Causes of infertility vary according to the age of the couples and age of marriage. Although PCOS remains the main cause, infections are a major cause of tubal factor infertility, and tobacco and alcohol worsen the male factor. One-third of the cases still remain unexplained.